Evaluation Report on the Fishing Harbour Projects - Planning Commission (Planning Commission, 1981)
The Programme Evaluation Organisation of the Planning Commission conducted at the instance of the Ministry of Agriculture and Rural Reconstruction, Government of India, during 1979-80 an evaluation study of five Fishing Harbour projects viz, Cochin (Kerala), Karwar (Karnataka), Port. Blair (Andaman and Nicobar Islands), Tuticorin (Tamil Nadu) and Visakhapatnam (Andhra Pradesh). Of these, Cochin and Visakhapatnam are in the category of major fishing harbours whereas Karwar, Pert Blair and Tuticorin are minor fishing harbours.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India